The interrelationships of parenting and children's temperament: Implications for emotional and social problems - Waters, A; Zimmer-Gembeck, M (My University, 2007)
Using data from 'Growing Up in Australia: the Longitudinal Study of Australian Children' (LSAC), the authors explore the unidirectional relationships between parenting, child temperament, and children's socio-emotional and behavioural outcomes. The authors analyse the effect of parenting and child temperament on child outcomes (including problems, competence, and emotional and social functioning), the effect of parenting dimensions (self-efficacy, warmth, hostility) on child temperament (such as persistence and reactivity), and the effect of infant temperament (such as cooperativeness and irritability) on parenting style. The presentation features charts and slides outlining the methodology and measures, regression modeling, the results, and models illustrating the relationship pathways.
Keywords: Families; Child Development; Families -- Parents and Parenting; Families and relationships; Childhood and child development; Families; Child Development; Parents and Parenting; Families and relationships; Childhood and child development